Transcriptome Profiles of Highly Pathogenic Pure Avian H7N9 Virus-Infected Lungs of BALB/c Mice - Gong, Wenxiao; Huang, Kun; Zhang, Yufei; He, Xinglin; Li, Chengfei; Mao, Haiying; Wei, Yanming; Zou, Zhong; Jin, Meilin (Frontiers in Veterinary Science, 2020)
Avian influenza A (H7N9) viruses emerged in China in 2013 and cause a zoonotic disease associated with a high case-fatality ratio of over 30%. Transcriptional profiles obtained using animal models reveal host responses to the disease, thereby providing insights into disease pathogenesis. Therefore, we aimed to characterize the host responses of H7N9 virus infected-mouse lungs in this study. First, we isolated an avian-originated H7N9 strain, which was shown to be highly pathogenic to both chicken and mice. Genomic analysis results suggested that a 12-nucleotide-insertion was present at the hemagglutinin (HA) cleavage site and both the HA and neuraminidase (NA) genes belonged to the Yangtze River Delta lineage. RNA sequencing results revealed 566 differentially expressed genes (DEGs) in the H7N9-infected lungs. Moreover, transcriptome analysis revealed that over-activated antiviral signals and intense interferon (IFN)-stimulated gene products possibly contributed to the high virulence of the virus in mice. Importantly, lung concentrations of inflammatory cytokines, including interleukin (IL)-1β, IL-6, IFN-β, and tumor necrosis factor (TNF)-α, were upregulated in response to H7N9 virus infection. Overall, the present study provided a comprehensive understanding of H7N9 virus pathogenicity and correlated host immune responses.